How to do everything with Windows Vista - Simmons, Curt, 1968- (Emeryville, Calif. : McGraw-Hill/Osborne ; London : McGraw-Hill [distributor], 2007)
Bring clarity to your PC experience with Windows Vista and this easy-to-use guide. How to Do Everything with Windows Vista shows you how to take full advantage of all the powerful and fun features of this revolutionary new operating system. Learn to customize your settings, connect to the Internet, set up a home network, secure your system, and connect peripheral devices. You'll also discover how to maximize all of the entertainment capabilities--games, music, photos, video, and more. Manage components, programs, folders, and files, Install hardware and software, Use printers, scanners, and digital cameras, Connect to the Internet, Set up and manage a home network, Manage security with Windows Firewall and Windows Defender, Play games on your PC or online, Play and record music with Windows Media Player, Create your own movies with Windows Movie Maker, Organize and print your digital photos, Optimize, manage, and troubleshoot Windows Vista.
Acknowledgments -- Introduction -- Get to Know Windows Vista -- Explore the Vista Desktop -- Start Your Computer -- Get to Know Your Windows Vista Desktop -- Check Out the Recycle Bin -- Manage Your Taskbar -- Explore the Start Menu to Get to All the Programs -- Log Off Your Computer -- Restart or Turn Off Your Computer -- Manage Your Computer with the Control Panel -- Open the Control Panel -- Add Hardware -- Administrative Tools -- AutoPlay -- Backup and Restore Center -- BitLocker Drive Encryption -- Color Management -- Date and Time -- Default Programs -- Device Manager -- Ease of Access -- Folder Options -- Fonts -- Game Controllers -- Indexing Options -- Internet Options -- iSCSI Initiator -- Keyboard -- Speed -- Hardware -- Mail -- Mouse -- Buttons -- Pointers -- Pointer Options -- Wheel -- Hardware -- Network and Sharing Center -- Offline Files -- Parental Controls -- Pen and Input Devices -- People Near Me -- Performance Information and Tools -- Personalization -- Phone and Modem Options -- Power Options -- Printers -- Problem Reports and Solutions -- Programs and Features -- Regional and Language Options -- Scanners and Cameras -- Security Center -- Sound -- Speech Recognition -- Sync Center -- System -- Tablet PC Settings -- Taskbar and Start Menu -- Text to Speech -- User Accounts -- Welcome Center -- Windows CardSpace -- Windows Defender -- Windows Firewall -- Windows Sidebar -- Windows Sideshow -- Windows Update -- Personalize Your Computer -- Customize Your Start Menu and Taskbar -- Use the Start Menu -- Customize the Start Menu -- Customize the Taskbar -- Configure Your Display -- Display Settings -- Window Color and Appearance -- Desktop Background -- Screen Saver -- Sounds -- Mouse Pointers -- Theme -- Configure Folder Views -- General -- View -- Search -- Configure Folder Views -- Windows Sidebar -- Starting and Configuring the Sidebar -- Working with Gadgets -- Manage Components, Programs, Folders, and Files -- Manage Programs with Windows Vista -- Install a New Program -- Uninstall a Program -- Use Windows Vista's Compatibility Mode -- Manage Windows Vista Components -- Turn On a Windows Feature -- Turn Off a Windows Feature -- Manage Folders and Files -- Create, Rename, and Delete Folders -- Use Folder Menu Options -- View Menu -- Use Folder Compression -- Create a Compressed Folder -- Add Items to and Remove Them from a Compressed Folder -- Use Extraction -- About Files -- Use the Accessories that Come with Windows -- Calculator -- Command Prompt -- Connect to a Network Projector -- Notepad -- Paint -- Remote Desktop Connection -- Run -- Snipping Tool -- Sound Recorder -- Sync Center -- Welcome Center -- Windows Explorer -- Windows Sidebar -- WordPad -- Ease of Access -- System Tools -- Tablet PC -- Manage Hardware -- Understand Hardware -- The Golden Rules of Windows XP Hardware -- Install a Plug-and-Play Device -- Remove a Plug-and-Play Device from Your Computer -- Install a Non-Plug-and-Play Device -- Use Device Manager -- Examine a Device's Properties -- Windows Update Driver Settings -- Hardware Troubleshooting Tips -- Use Printers, Scanners, and Digital Cameras -- Check Out the Printers Folder -- Install a New Printer -- Configure Your Printer -- Manage Print Jobs -- Troubleshoot Common Printer Problems -- Use Fax Support in Windows Vista -- Use Scanners and Digital Cameras with Windows Vista -- Install Scanners and Cameras -- Manage Scanner and Camera Properties -- Get Connected -- Create Connections to the Internet -- Internet Connections 101 -- Connecting with a Dial-Up Connection -- Connecting with a Broadband Connection -- Configure Your Modem -- Install a Modem -- Configure Modem Properties -- Create Connections to the Internet -- Surf the Internet -- Understand Internet Terms and Technology -- Understand the Internet Explorer Interface -- Favorites -- Tabs -- Home -- Feeds and Print -- Page -- Tools -- Configure Internet Explorer Through Internet Options -- General Tab -- Security Tab -- Privacy Tab -- Content Tab -- Connections Tab -- Programs Tab -- Advanced Tab -- Run Windows Mail -- How E-Mail Works -- Set Up Windows Mail -- Check Out the Windows Mail Interface -- Send and Receive E-Mail -- Send an E-Mail -- Attach a File to an E-Mail -- Receive Messages -- Receive Attachments -- Change Windows Mail Views -- Create Message Rules -- Create a New Rule -- Manage Message Rules -- Block Senders -- What Happened to Identities? -- Manage Your Accounts -- Customize Windows Mail -- Create a Home Network -- Windows Networking Basics -- Plan Your Home Network -- Understand Internet Connection Sharing -- Use the Setup a Network Wizard -- Set Up Your ICS Clients -- Internet Explorer -- Set Up a Wireless Network -- Use Windows Vista on a Large Network -- Virtual Private Networking -- Configure Your Windows Vista Computer for a VPN Connection -- Network File and Printer Sharing -- Manage Users and Groups -- Understand User Accounts -- Manage User Accounts -- Create a New Account -- Change an Account -- Manage User Accounts with Computer Management -- Manage Groups -- Windows Vista Security and Remote Connections -- Use Windows Firewall -- Issues with Windows Firewall -- Checking Windows Firewall -- Configure Windows Firewall Settings -- Use Windows Defender -- Run a Scan -- Use Windows Defender Tools -- Configure Parental Controls -- Setting Up Parental Controls -- Configure Remote Desktop -- Enable Remote Desktop -- Configure the Remote Desktop Client Computer -- Make a Remote Desktop Connection -- Manage Remote Desktop Performance -- Use Remote Assistance -- Turn On Remote Assistance -- Request Remote Assistance -- Cool Things You Can Do with Windows Vista -- Play Games -- Manage Game Controllers -- Play Games with Windows XP -- Playing Games Installed with Windows Vista -- Playing Games on the Internet -- Installing and Playing Your Own Games -- Troubleshooting Game Problems -- A Game Controller Doesn't Work -- DirectX Problems -- Game Lockup -- Set Display Mode: DDERR_GENERIC -- Use Volume Controls and Sound Recorder -- Use Windows Media Player -- Now Playing -- Library -- Adding an Item to the Library -- Creating a Playlist -- Rip -- Burn -- Sync -- Skin Chooser -- Media Player Configuration Options -- Create Movies with Windows Movie Maker -- Why Use Windows Movie Maker? -- Opening Windows Movie Maker -- Importing Digital Data -- Importing from a DV Camera -- Importing Existing Video or Pictures on Your Computer -- Make Movies -- Splitting Clips -- Combining Clips -- Getting Familiar with the Workspace -- Trimming Clips -- Creating Transitions -- Add Audio to Your Movies -- Adding Audio -- Adding Titles and Credits -- Save Movies -- Publishing Your Movie -- Manage Digital Photos and Use Windows Slideshow -- Connect to Your PC -- View and Manage Your Photos -- Use the Photo Gallery -- File -- Fix -- Info -- Print -- E-Mail -- Burn -- Make a Movie -- Open -- Control Toolbar -- Print Your Photos -- Burn Your Photos to a CD -- Use Windows Slideshow -- Take Care of Windows Vista -- Hard Disk Basics -- File System Basics -- FAT32 -- NTFS -- Set Hard Disk Properties -- General Tab -- Tools -- Hardware -- Sharing -- Security -- Previous Versions -- Quota -- Schedule Tasks -- Create a Task -- Use Windows Update -- Optimize, Troubleshoot, and Fix Windows Vista -- Manage Disks -- Manage Disks -- Understanding Dynamic Disks -- Understanding Disk Status -- Formatting a Disk -- Creating a New Volume -- Assigning a Different Drive Letter and Path to a Volume -- Extending or Shrinking a Volume -- Other Volume Solutions -- Use Windows Vista Backup and Restore -- Backing Up Data -- Restoring Data -- BitLocker Drive Encryption -- Solve Problems with Windows Vista -- Performance Information and Tools -- Use System Information -- System Summary -- Hardware Resources -- Components -- Software Environment -- Use the Reliability and Performance Monitor -- Reliability and Performance Monitor Interface -- Using the Performance Monitor -- Reliability Monitor -- Use System Properties to Optimize Windows Vista -- Performance Options -- Troubleshooting Tips -- Using CTRL-ALT-DEL -- Use Windows Help -- Use Safe Mode -- Use System Restore -- Running System Restore -- Install Windows Vista -- Upgrade to Windows Vista -- Check the System Requirements -- Back Up Your Data -- Check Out Your Device Drivers -- Check for Viruses and Disable Antivirus Software -- Shut Down All Programs -- Upgrade to Windows Vista -- Install Windows Vista as a New Installation -- Prepare for a Clean Installation -- Activate Windows Vista -- Index -- Table of Contents provided by Ingram. All Rights Reserved.
Includes index.
1
Keywords: CIT; Operating systems; Microsoft Windows (Computer file)